If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x-7)+5=-(9-2x)
We simplify the equation to the form, which is simple to understand
2(x-7)+5=-(9-2x)
Reorder the terms in parentheses
+(+2x-14)+5=-(9-2x)
Remove unnecessary parentheses
+2x-14+5=-(+9-2x+)
Remove unnecessary parentheses
+2x-14+5=-9+2x
We move all terms containing x to the left and all other terms to the right.
+2x-2x=-9+14-5
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| 9x^2+3x-16=0 | | 4x+17-8x=20-15x+11x-3 | | 10m=3m | | m-2=6m+12 | | 8y+5=7y-4 | | 3/2*b+8=20 | | 6(5x-2)=26 | | 12-3*8-2=-6 | | 3.1x+4.6=108 | | 0.7x+0.5(20)=0.4(x+40) | | 4(a-3)+3a=16 | | q=5q^2+10 | | ((y^3+3y)/(y^2-9))/((y^2+11y+30)/(y^2+2y-15)) | | p=20-p | | 16=3(x-1)-(x-5) | | 3(4c-1)-2=7c+5 | | 4(3x-8)-3=4(x-3)-7 | | 6x-(7x+7)=3x-47 | | 4y-7=10y+29 | | -2(t+5)=0 | | 10x+100=7x+12 | | 8x-1=6x-39 | | 4x+68=7x-13 | | 34-19=3(x-2) | | 40+5y-7=16y-12-2y | | x*6+115=x*15-11 | | 52=x+27 | | x+23+3x=-20-3x-27 | | 92-4x=14x+22 | | 9x^2=21x | | 2x+20=4x+6 | | x(3x-2)(x+6)= |